A Single Dose of Dietary Nitrate Increases Maximal Knee Extensor Angular Velocity and Power in Healthy Older Men and Women - Coggan, Andrew R; Hoffman, Richard L; Gray, Derrick A; Moorthi, Ranjani N; Thomas, Deepak P; Leibowitz, Joshua L; Thies, Dakkota; Peterson, Linda R (The journals of gerontology. Series A, Biological sciences and medical sciences, 2020)
Aging results in reductions in maximal muscular strength, speed, and power, which often lead to functional limitations highly predictive of disability, institutionalization, and mortality in elderly adults. This may be partially due to reduced nitric oxide (NO) bioavailability. We, therefore, hypothesized that dietary nitrate (NO3-), a source of NO via the NO3- → nitrite (NO2-) → NO enterosalivary pathway, could increase muscle contractile function in older subjects. Twelve healthy older (age 71 ± 5 years) men and women were studied using a randomized, double-blind, placebo-controlled, crossover design. After fasting overnight, subjects were tested 2 hours after ingesting beetroot juice containing or devoid of 13.4 ± 1.6 mmol NO3-. Plasma NO3- and NO2- and breath NO were measured periodically, and muscle function was determined using isokinetic dynamometry. N O 3 - ingestion increased (p < .001) plasma NO3-, plasma NO2-, and breath NO by 1,051% ± 433%, 138% ± 149%, and 111% ± 115%, respectively. Maximal velocity of knee extension increased (p < .01) by 10.9% ± 12.1%. Maximal knee extensor power increased (p < .05) by 4.4% ± 7.8%. Acute dietary NO3- intake improves maximal knee extensor angular velocity and power in older individuals. These findings may have important implications for this population, in whom diminished muscle function can lead to functional limitations, dependence, and even premature death.